Independent effects of reported sexually transmitted infections and sexual behavior on HIV-1 prevalence among adult women, men, and teenagers in rural Uganda. - Carpenter, L; Kamali, A; Payne, M; Kiwuuwa, S; Kintu, P; Nakiyingi, J; Kinsman, J; Nalweyiso, N; Quigley, M; Kengeya-Kayondo, J; Whitworth, J (2002)
OBJECTIVE: To assess whether sexually transmitted infections (STIs) and sexual behavior are independently associated with HIV-1 among adult women, men, and teenagers in rural Uganda. DESIGN: Cross-sectional survey. METHODS: All adults (13 years and older) residing in 18 communities were invited to participate. HIV status was determined from serum samples and data collected during confidential interview. Independent effects of risk factors for HIV were estimated using adjusted odds ratios (ORs) with 95% confidence intervals (CIs) from logistic regression. RESULTS: Women reporting genital ulcers in the last 12 months were over twice as likely to be HIV positive after adjustment for sociodemographic factors and number of lifetime sexual partners (OR, 2.5; 95% CI, 1.9-3.4). Equivalent associations were stronger for men (OR, 3.2; 95% CI, 2.2-4.7) but weaker for teenagers (OR, 2.0, 95% CI, 0.5-8.7). Number of lifetime sexual partners was associated ( p <.05) with HIV status for women, men, and teenagers independently of reported genital ulcers. Teenagers reporting casual partners were over four times ( p <.001), and men reporting condom use almost twice ( p <.001), as likely to be HIV positive. Neither history of genital discharge nor other measures of sexual behavior were independently related to HIV status. CONCLUSION: Reported STIs and sexual behavior are independently associated with HIV in rural Uganda. Community-based interventions to reduce HIV should target both and should include teenagers.